Regulation of the Expression of SARS-CoV-2 Receptor Angiotensin-Converting Enzyme 2 in Nasal Mucosa - Takabayashi, Tetsuji; Yoshida, Kanako; Imoto, Yoshimasa; Schleimer, Robert P; Fujieda, Shigeharu (American journal of rhinology & allergy, 2022)
Coronavirus disease 2019 (COVID-19) has caused a global pandemic. Higher expression of the virus receptor angiotensin-converting enzyme 2 (ACE2) in the nasal mucosa may be associated with high transmissibility and asymptomatic infection. In COVID-19, the elucidation of the determinants of ACE2 expression at nasal tissue level is crucial. The development of strategies to downregulate ACE2 expression in nasal epithelial cells might reduce transmission and be useful as a novel therapeutic approach. To verify ACE2 expression in the nasal mucosa of patients with seasonal allergic rhinitis induced by Japanese cedar pollen (SAR-JCP) and chronic rhinosinusitis with nasal polyp (CRSwNP) and to examine the effects of short-chain fatty acids (SCFAs) on ACE2 expression in airway epithelial cells. We assessed ACE2 expression in the nasal mucosa of control subjects, patients with SAR-JCP, and those with CRSwNP using real-time polymerase chain reaction. We also quantified ACE2 gene expression in cultured airway epithelial cells. Although ACE2 expression was greatly increased in a few patients with SAR-JCP during the Japanese cedar pollen season, mean levels were not significantly increased. ACE2 mRNA expression was significantly decreased in nasal polyp tissue from patients with chronic rhinosinusitis compared with the expression in that from control subjects. SCFAs generated by gastrointestinal microbiota significantly reduced resting ACE2 expression in cultured airway epithelial cells. SCFAs also significantly suppressed the dsRNA-dependent upregulation of ACE2 expression in airway epithelial cells. Inflammatory endotype affects ACE2 expression in the nasal mucosa and influences susceptibility to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. In particular, type 2 inflammation could downregulate ACE2 expression in the nasal mucosa and reduces susceptibility to SARS-CoV-2 in patients with CRSwNP. Although in vivo experiments are required, administration of SCFAs to the nasal cavity might be worthy of consideration as a preventative or therapeutic strategy for the early-stage COVID-19.